Estimation of Skeletal Muscle Mass Relative to Adiposity Improves Prediction of Physical Performance and Incident Disability. (29th July 2017) - Baker, Joshua F; Long, Jin; Leonard, Mary B; Harris, Tamara; Delmonico, Matthew J; Santanasto, Adam; Satterfield, Suzanne; Zemel, Babette; Weber, David R
Abstract: Purpose: We assessed the discrimination of lean mass estimates that have been adjusted for adiposity for physical functioning deficits and prediction of incident disability. Methods: Included were 2, 846 participants from the Health, Aging and Body Composition Study with available whole-body dual energy absorptiometry measures of appendicular lean mass index (ALMI, kg/m 2 ) and fat mass index (FMI, kg/m 2 ). Age-, sex-, and race-specific Z -Scores and T -Scores were determined by comparison to published reference ranges. ALMI values were adjusted for FMI (ALMIFMI ) using a novel published method. Sex-stratified analyses assessed associations between lean mass estimates and the physical performance score, ability to complete a 400-meter walk, grip strength, and incident disability. Dichotomized definitions of low lean for age and sarcopenia were examined and their performance compared to the ALM-to-BMI ratio. Results: Compared to ALMI T -Scores and Z -Scores, the ALMIFMI scores demonstrated stronger associations with physical functioning, and were similarly associated with grip strength. Greater FMI Z -Scores and T -Scores were associated with poor physical functioning and incident disability. Definitions of low lean for age and sarcopenia using ALMIFMI (compared to ALMI) better discriminated those with poor physical functioning and a greater risk of incident disability. The ALM-to-BMI ratio was modestly associated with grip strength and physical performance, but was not associated with completion of the 400-meter walk or incident disability, independent of adiposity and height. Conclusion: Estimation of skeletal muscle mass relative to adiposity improves correlations with physical performance and prediction of incident disability suggesting it is an informative outcome for clinical studies.